2014
DOI: 10.1002/mnfr.201300936
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable effect of trigonelline, an alkaloid present in coffee and fenugreek, on bone mechanical properties in estrogen‐deficient rats

Abstract: Scope Trigonelline (1‐methylpyridinium‐3‐carboxylate), an alkaloid present in coffee and fenugreek seed, has been reported to exhibit phytoestrogenic activity. The aim of the present study was to investigate the effects of trigonelline on bone mechanical properties of rats with normal estrogen level and estrogen deficiency (developing osteoporosis). Methods and results The experiments were performed on 3‐month‐old nonovariectomized and ovariectomized (estrogen‐deficient) Wistar rats, divided into control rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 36 publications
2
26
0
1
Order By: Relevance
“…Plant extracts contain diosgenin mainly as glycosides (saponins); they also include other, various components (like flavonoids or alkaloids) which may exert their own effects on the skeletal system. For example, in studies performed parallelly to the study reported here, we observed that fenugreek seed (1% in the diet) tended to favorably affect the rat skeletal system, whereas at a higher dose (administered as an (Folwarczna et al, 2014a), to which trigonelline could contribute (Folwarczna et al, 2014b). Effects of diosgenyl saponins may also differ from those of diosgenin, due to, among others, different bioavailability.…”
Section: Discussionsupporting
confidence: 51%
“…Plant extracts contain diosgenin mainly as glycosides (saponins); they also include other, various components (like flavonoids or alkaloids) which may exert their own effects on the skeletal system. For example, in studies performed parallelly to the study reported here, we observed that fenugreek seed (1% in the diet) tended to favorably affect the rat skeletal system, whereas at a higher dose (administered as an (Folwarczna et al, 2014a), to which trigonelline could contribute (Folwarczna et al, 2014b). Effects of diosgenyl saponins may also differ from those of diosgenin, due to, among others, different bioavailability.…”
Section: Discussionsupporting
confidence: 51%
“…The aim of Folwarczna J. et al study was to investigate the effects of trigonelline, an alkaloid present in coffee, on bone mechanical properties of rats with normal estrogen level and estrogen deficiency. Administration of trigonelline did not affect the bone turnover markers, bone mineralization and mechanical properties of the tibial metaphysis, femoral diaphysis, and femoral neck in non-ovariectomized rats, but it worsened the mineralization and mechanical properties of cancellous bone in ovariectomized rats (estrogen-deficient rats) (23). The results of Folwarczna J. et al study showed that caffeine has favorably affected on the skeletal system of ovariectomized rats, slightly inhibiting the development of bone changes induced by estrogen deficiency.…”
Section: Discussionmentioning
confidence: 93%
“…Data from animal studies are also inconsistent (9,10). In animal studies the influence of individual constituents of coffee on bone tissue was examined (23,24). The aim of Folwarczna J. et al study was to investigate the effects of trigonelline, an alkaloid present in coffee, on bone mechanical properties of rats with normal estrogen level and estrogen deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Fenugreek (Trigonella foenum-graecum L.) is a medicinal plant having various properties, which include stimulation of lactation, aids digestion and improves metabolism and health [15,16]. Fenugreek seed contains at least three major constituents, which reported to affect the skeletal system.…”
Section: Resultsmentioning
confidence: 99%
“…Trigonelline an alkaloid from plants like coffee and fenugreek [15,16] known has various pharmacological activities have been attributed to trigonelline such as antioxidant, hypoglycemic, hypolipidemic, anti-migraine, anti-inflammatory, anti-ulcerogenic, antibacterial, antiviral, immunomodulator and anti-tumor activities [18,19,20]. 4-Hydroxyisoleucine, an amino acid characteristic of fenugreek, is considered responsible for antidiabetic and lipidlowering actions [21], together with galactomannan, trigonelline and diosgenin [22,23], antidiabetic drugs may exert differential effects on bones [24].…”
Section: Resultsmentioning
confidence: 99%